Targeting Interleukin-6 Signaling with Tocilizumab in Atherosclerosis: A Meta-Analysis of Anti-Inflammatory Effects and Plaque Stabilization - Ali Zainal Abidin; Tri Nisdian Wardiah; Taufik Indrajaya; Nur Riviati (Open Access Indonesian Journal of Medical Reviews, 2025)
Atherosclerosis, a chronic inflammatory disease, is the leading cause of cardiovascular disease. Interleukin-6 (IL-6) plays a crucial role in atherogenesis, making it a potential therapeutic target. Tocilizumab, an IL-6 receptor antagonist, has shown promise in reducing inflammation and stabilizing atherosclerotic plaques. This meta-analysis aimed to evaluate the efficacy and safety of tocilizumab in atherosclerosis by analyzing its impact on inflammatory markers and plaque characteristics. A systematic search of PubMed, Embase, and Cochrane Central Register of Controlled Trials was conducted from January 2013 to January 2024. Studies evaluating the effects of tocilizumab on inflammatory markers and plaque characteristics in patients with atherosclerosis were included. Randomized controlled trials (RCTs) and observational studies with a comparative arm were eligible. Data were extracted and pooled using a random-effects model. Nine studies (n=1248 participants) met the inclusion criteria. Tocilizumab significantly reduced CRP levels (standardized mean difference [SMD] -1.23; 95% confidence interval [CI] -1.56 to -0.90; p<0.001) and IL-6 levels (SMD -0.87; 95% CI -1.12 to -0.62; p<0.001) compared to control groups. A significant reduction in plaque volume (SMD -0.45; 95% CI -0.71 to -0.19; p=0.001) and an increase in fibrous cap thickness (SMD 0.38; 95% CI 0.12 to 0.64; p=0.004) were also observed. No significant increase in adverse events was reported in the tocilizumab group. This meta-analysis demonstrates that tocilizumab effectively reduces inflammation and promotes plaque stabilization in atherosclerosis. These findings suggest that tocilizumab may be a promising therapeutic strategy for preventing cardiovascular events in patients with atherosclerosis. Further large-scale RCTs are needed to confirm these findings and establish the long-term safety and efficacy of tocilizumab in this population.